1
vote
1answer
26 views

Laplace transform of integral equation

Use Laplace transforms to solve the integral equation $$y(t)-\frac{1}{2}\int_0^ty(t-v)~dv=1$$ First find the Laplace transform $Y(s)$ of $y(t)$
4
votes
3answers
183 views

A convolution like integral equation

I would like to solve the following integral equation for $g(z)$. $$\int_z^\infty g(\zeta)(\zeta-z)^{\alpha-1} d\zeta = e^{-bz}, \tag{1}$$ where $\alpha$ and $b$ are constants. I would also like to ...
0
votes
3answers
85 views

How to solve $y'+6y(t)+9\int_0^t y(\tau)d\tau=1$, $\,y(0)=0$

I want to solve this equation. It reminds me something about Laplace transform. I am sure that I must use it order to solve this: $$y'+6y(t)+9\int_0^t y(\tau)d\tau=1,\qquad y(0)=0$$
2
votes
1answer
104 views

Integral Equation without solution?

working on a physical problem I arrived at the following equation $$ y(x) + A \int_{0}^{x} e^{\lambda (t-x)} y(t) \mathrm{d}t = 0$$ and after some struggling (not that easy to apply the basic Laplace ...
3
votes
1answer
2k views

How to solve partial integro-differential equation?

Suppose the following partial integro-differential equation for a function $u(x,t)$ with $t\geq0$, $x \in [0,L]$: $\partial_t u = \partial_{xx} u + f(u,\lambda)$ $\lambda = B\left(u_0 - \int_{x=0}^L ...
1
vote
1answer
80 views

Laplace transform of convolution with modified limits

I have an expression such as $\int_0^{x+l}y(z)g(x-z) dz$ and I want to evaluate its Laplace transform w.r.t $x$ in terms of the Laplace transform of $y(x)$. I know that I can substitute $t=x+l$, and ...
2
votes
1answer
155 views

Laplace transform having this unusual property in convolution?

Here is the problem Solve $y'(t) = 1 - \int_{0}^{t} y(t - v)e^{-2v}dv$ The solution sets $\mathcal{L}(y) = Y(s)$ and does the following Notice that in step 1, they have $$Y(s)\dfrac{1}{s+2}$$ ...
4
votes
1answer
455 views

How to solve $t-2f(t) = \int_0^t(e^\tau- e^{-\tau})f(t-\tau)d\tau$

I want to solve this equation. It reminds me something about Laplace transform. I am sure that I must use it order to solve it. $$t-2f(t) = \int_0^t(e^\tau- e^{-\tau})f(t-\tau)d\tau$$ How to do it? ...